2020
DOI: 10.1111/jwas.12681
|View full text |Cite
|
Sign up to set email alerts
|

First report of Cyprinid herpesvirus 2 outbreak in cultured gibel carp, Carassius auratus gibelio at low temperature

Abstract: Cyprinid herpesvirus 2 (CyHV-2) is the causative agent of herpesviral hematopoietic necrosis (HVHN), an infectious disease with high morbidity and mortality worldwide. Current research indicates that CyHV-2 only infects fish in the genus Carassius. Outbreaks of fish viral diseases are highly temperature-dependent, and HVHN outbreaks usually occur at water temperatures of 15-25 C. In November 2018, an infectious disease occurred on cultured gibel carp farms in ZiGong, Sichuan Province, China. The water temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…CyHV-2 decreases its pathogenicity when the temperature exceeds 27°C (Goodwin et al 2009). Recently, Ouyang et al (2020) reported an outbreak of CyHV-2 disease in gibel carp, C. auratus gibelio at a non-permissive temperature of 10°C. The disease can cause severe mortality to all sizes of fish (Wu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…CyHV-2 decreases its pathogenicity when the temperature exceeds 27°C (Goodwin et al 2009). Recently, Ouyang et al (2020) reported an outbreak of CyHV-2 disease in gibel carp, C. auratus gibelio at a non-permissive temperature of 10°C. The disease can cause severe mortality to all sizes of fish (Wu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…After reaching a peak incidence in the population, the most common (clonal gynogenetic) phenotype is becoming more vulnerable to attacks by biological enemies than a far less frequent sexual population [ 106 ]. Herpesviral hematopoietic necrosis, caused by cyprinid herpesvirus-2, has affected many natural populations and commercial farms of gynogenetic Carassius biotypes [ 107 , 108 , 109 , 110 , 111 ]. The Red Queen hypothesis predicts evolution towards equilibrium in the populational composition of sexual and asexual biotypes coexisting together and co-evolving with parasites.…”
Section: Equilibrium Between Quantitative Gynogenesis and Qualitative...mentioning
confidence: 99%
“…After reaching a peak incidence in the population, the most common (clonal gynogenetic) phenotype is becoming more vulnerable to attacks by biological enemies than a far less frequent sexual population [102]. Herpesviral hematopoietic necrosis, caused by cyprinid herpesvirus-2, has affected many natural populations and commercial farms of gynogenetic Carassius BIOTYPES [103][104][105][106][107]. The Red Queen hypothesis predicts evolution towards equilibrium in populational composition of sexual and asexual BIOTYPES coexisting together and co-evolving with parasites.…”
Section: Equilibrium Between Quantital Gynogenesis and Qualital Sexua...mentioning
confidence: 99%